Thai International Students' Experiences in Studying Islamic Education in Indonesia: Challenges and Opportunities - Kunaepi, Aang; Yusuf Isnan Setiawan, Akhmad; Nasikhin, Nasikhin (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This study explores the experiences of international students from Thailand in pursuing Islamic Religious Education in Indonesia, focusing on the challenges and opportunities faced. Using a qualitative approach with a case study design, data were obtained through observation, interviews, and case study analysis using the Cresswell (2016). The results of the study revealed that students faced major obstacles in the form of limitations in understanding the language of instruction, local cultural differences, and difficulties in understanding contextual religious terminology. Barriers to integrating technology into Islamic Education learning also exacerbated the existing challenges. However, significant opportunities also emerged, such as enriching religious knowledge through comparing theological perspectives, openness to religious interpretations, and learning experiences in an inclusive multicultural environment. In addition, limited support from peers and lecturers also helped Thai students overcome these obstacles. The contribution of these findings lies in a deeper understanding of the dynamics of religious learning in a cross-cultural context and the importance of adapting more inclusive teaching strategies. The results of this study can be a basis for educational institutions in designing learning programs that support international students, especially in overcoming linguistic, cultural, and technological challenges, in order to improve the quality of their learning experience in Indonesia.